The Large Synoptic Survey Telescope: Overview and Update: Invited Talk. Issue Volume 14:Issue S339(2018) (November 2017) - Graham, M. L.
Abstract: This talk provided an overview and update of the LSST Project and a review of the Data Management system, with a focus on the products most relevant to the researchers of transients and variables. The open opportunities for user-defined Special Programmes such as Deep Drilling Fields were also presented.